Cracks beyond the limits: Are they a problem in XS2? - Polder Rob; Elsener Bernhard (MATEC Web of Conferences)
The maximum design crack width under normal environmental conditions is given as 0.3 mm, supposed to prevent corrosion of reinforcement. We discuss the consequences when this limit is applied to permanently submerged reinforced concrete structures in sea water (XS2), taking into account that in permanently submerged concrete, there is insufficient oxygen to support significant corrosion. One case concerns permanently submerged harbour quay slabs. Calculated bending crack widths were above the limit of 0.3 mm and additional reinforcement was deemed needed. Assuming that oxygen transport was limited, the corrosion risk was considered negligible and adding reinforcement was not necessary. Another case concerns caissons in shallow sea water built by slipforming. The slipforming caused some “lifting” cracks above 0.3 mm surface width. In the submerged parts, oxygen diffusion through sea water inside the cracks is so slow that corrosion was insignificant over the required 100-year service life; costly injection was not needed. It should be noted that significant corrosion is possible if macro-cells can form, e.g. in hollow-leg structures where cathodic oxygen reduction on the aerated inside may support corrosion in cracks on the outside. Under those conditions high corrosion rates are possible; such cracks should be avoided or repaired.